The Effect of Addition of Agave Sisalana Fiber and Sikacim Concrete Additive on Tensile Strength and Concrete Absorption - Fahrizal Zukarnain; Kurniawan Syaputra; Sri Frapanti; Rizki Efrida; Ahmad Marabdi Siregar; Ika Pratiwi Pujianti; Hilda Nisti Zendrato (Rekayasa Material, Manufaktur dan Energi, 2022)
This paper presents an experimental study that was carried out to determine the potential of natural fiber Agave Sisalana and sikacim concrete additive chemicals on concrete used as construction materials. The concrete mix ratio 1: 1,34: 2,37 was prepared using a water-cement factor of 0,45. Sikacim concrete additive is added as much as 0,8% of the cement weight and a reduction of water as much as 15%. The Agave Sisalana fiber added as much as 0,3% and 0,6% of cement weight. Tensile strength concrete testing was carried out at the age of 21 and 28 days. The experiment result indicated that the tensile strength and water absorption in concrete increase with the addition of Agave Sisalana Fiber and sikacim concrete additive. Thus, the Agave Sisalana Fiber and Sikacim Concrete Additive can be used as an additive in concrete mixing to increase tensile strength.